Book Review of McGee, Ebony. O. Black, Brown, Bruised: How Racialized STEM Education Stifles Innovation. (14th October 2022) - Laosebikan, Olanipekun
Abstract : Essay review of McGee, Ebony. O. Black, brown, bruised: How racialized STEM education stifles innovation . Cambridge, MA: Harvard Education Press, 2020. Pp.190.